Etnis Tionghoa dan Jawa : Cara Pandang Mereka dalam Mempersiapkan Suksesor Bisnis Keluarga - Meida Rachmawati; Ignatius Hari Santoso (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
This study aims to examine the difference attitude between Indonesian Chinese and Indonesian Javanese in term of family business successor planning.. Sample used in this researh is came from Javanese and Indonesian Chinese businessman in Semarang. Data retrieval is done by using open-ended questionnaire, and being processed by SPSS ver 19.. The results of the study show that there is a significant difference between Indonesian Javanese and Indonesian Chinese in case of the way they prepare their family business successor.